Analisis Risiko operasional Kapal Tunda Menggunakan Metode FMEA - Muhammad Rafii Praswad; Irma Rustini Aju; Aditya Maharani (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
This company is a company engaged in shipping services in Indonesia. In supporting the efficiency and effectiveness of guiding operations, delays, and supporting facilities is to improve the quality of planning, scheduling, and digitalization of job order administration, so that the expectations of service users can be met. Every business process certainly has risks that may occur, including risks in the tugboat operational process. This research was conducted to anticipate operational risks in tugboat in the operational activities of tugboats and provide a proposed risk mitigation strategy to reduce the impact of risks that can occur. This research uses the Failure Mode and Effect Analysis (FMEA) method to determine the priority risks of tugboat operational activities and Fault Tree Analysis (FTA) to find the root causes of priority risks and design proposed risk mitigation strategies. The results of risk analysis using the Failure Mode and Effect Analysis (FMEA) method obtained 21 sub-risks from 4 categories. Seven sub-risks were prioritized based on the risk matrix. Seven priority sub-risks were analyzed using Fault Tree Analysis (FTA) to find the root cause of each sub-risk. So that the right risk handling strategy is proposed through interviews with experts.